Dampak Kebijakan Local Currency Settlement terhadap Perdagangan Internasional: Studi Kasus Indonesia-Jepang - Ghifari, Davin Athallariq; Syarif, Akbar Maulana; Zakaria, Rinny Apriliani; Rahajuni, Dijan (Sosio e-Kons, 2025)
This study analyzes the impact of the Local Currency Settlement (LCS) policy on international trade between Indonesia and Japan. LCS is a policy that enables both countries to conduct trade transactions using their local currencies, namely the Rupiah and Yen, with the aim of reducing dependence on the US dollar. This research employs a quantitative approach utilizing secondary data from 2000 to 2023. A multiple linear regression method is used to assess the influence of exchange rates, economic growth, and the LCS policy on the Indonesia-Japan trade balance. The findings indicate that the implementation of LCS has the potential to improve the trade balance, although the results are not statistically significant at the 95% confidence level. Nevertheless, positive indications are observed in terms of reduced transaction costs and increased bilateral trade volume. This research supports the theory of dedollarization and the diversification of the international monetary system as strategies to mitigate the risks associated with dollar volatility and to strengthen domestic economic stability in both Indonesia and Japan.